Kinetic behavior of quaternary ammonium hydroxides in mixed methane and carbon dioxide hydrates - Khan, M.S. (MDPI AG, 2021)
This study evaluates the kinetic hydrate inhibition (KHI) performance of four quaternary ammonium hydroxides (QAH) on mixed CH4 + CO2 hydrate systems. The studied QAHs are; tetraethylammonium hydroxide (TEAOH), tetrabutylammonium hydroxide (TBAOH), tetramethy-lammonium hydroxide (TMAOH), and tetrapropylammonium hydroxide (TPrAOH). The test was performed in a high-pressure hydrate reactor at temperatures of 274.0 K and 277.0 K, and a concentration of 1 wt. using the isochoric cooling method. The kinetics results suggest that all the QAHs potentially delayed mixed CH4 + CO2 hydrates formation due to their steric hindrance abilities. The presence of QAHs reduced hydrate formation risk than the conventional hydrate inhibitor, PVP, at higher subcooling conditions. The findings indicate that increasing QAHs alkyl chain lengths increase their kinetic hydrate inhibition efficacies due to better surface adsorption abilities. QAHs with longer chain lengths have lesser amounts of solute particles to prevent hydrate formation. The outcomes of this study contribute significantly to current efforts to control gas hydrate formation in offshore petroleum pipelines. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.